2017
DOI: 10.1039/c7nj01921a
|View full text |Cite
|
Sign up to set email alerts
|

A new pyrene cored small organic molecule with a flexible alkyl spacer: a potential solution processable blue emitter with bright photoluminescence

Abstract: A new pyrene cored small organic molecule viz., 1,3,6,8-tetrakis(4-((5-(9H-carbazol-9yl)pentyl)oxy)phenyl)pyrene (PY-II) was designed and synthesized. The carbazole moiety with alkyl spacer was introduced at 1, 3, 6 and 8 positions of pyrene core to improve the charge transport properties and solution processability. PY-II exhibited excellent solubility in common organic solvents and high thermal stability up to 345 o C. The photoluminescence quantum yield (PLQY) of PY-II in solution was found to be 0.9 with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The PE reported was 0.17 lm • W −1 , with 0.41 cd/A current efficiency and 202 cd/m 2 maximum brightness. 47 Bishnoi et al reported novel non-planar phenothiazine-5-oxides based on the donor, acceptor, and spacer concept compounds 2a-I (Figure 21). The synthesized compounds showed blue and blue-green emission in solution and in the solid state.…”
Section: Progress Of Blue Light Emitters In Indiamentioning
confidence: 99%
“…The PE reported was 0.17 lm • W −1 , with 0.41 cd/A current efficiency and 202 cd/m 2 maximum brightness. 47 Bishnoi et al reported novel non-planar phenothiazine-5-oxides based on the donor, acceptor, and spacer concept compounds 2a-I (Figure 21). The synthesized compounds showed blue and blue-green emission in solution and in the solid state.…”
Section: Progress Of Blue Light Emitters In Indiamentioning
confidence: 99%
“…The components of the chosen dyad (carbazole derivative and pyrene) were selected because they play a pivotal role in many areas of photophysics and optoelectronics. These popular polycyclic aromatic hydrocarbons and their various derivatives (including silicon-based carbazole , and pyrene-containing compounds ) have found application in optoelectronics, solar cells, TADF and organic light-emitting diode (OLED) materials, or fluorescent probes for elucidation of the geometries of various biomolecules. , There are also interesting studies that report white-light emission from pyrene-based compounds, and many of them are related to aggregation-induced emission. Furthermore, there are known examples of carbazole–pyrene hybrid compounds for dye-sensitized solar cell applications, OLEDs, and electroluminescent devices …”
Section: Introductionmentioning
confidence: 99%